The Soviet Union-Iraq relations during the Second Gulf War (1990-1991) is a political-historical study. - محەمەد, كەمال عەلی; محەمەد, هەستیار محەمەد عەلی سەید (Sulaimani Journal for Humanities, 2020)
The relationship between the Soviet Union and Iraq between the years 1990-1991 is the subject of this research, given the importance of the period of history of Iraq and their relations with the Soviets, which coincided with the emergence of signs of weakness and disintegration of the Soviet Union and the Iraqi invasion of Kuwait, in those years the Soviet foreign policy and its effects shrank and become And its republic is riding one hill and the other, and the socialist system is collapsing in Europe itself. When the Iraqi government mobilized its army on the border with Kuwait and invaded it, the Soviets only warned Iraq of the positions of that war and did not help Iraq in its campaign despite the historical relations between the two countries, but in spite of the failure of Iraq, at the | 186 jzsb.univsul.edu.iq JZSB p-ISSN: 1813-0852, e-ISSN: 2617-3034 گۆڤاری زانکۆی سلێمانی - (بهشی B - زانسته مرۆڤایهتییهکان) same time did not participate By sending Soviet military forces to cooperate with the United States and its allies to release Iraq from Kuwait. We have divided this research topic: The first topic: the title of this research (the dissolution of the Soviet Union 1990-1991), in which we talked about the end of that state and its collapse as a superpower competing with the United States of America at all levels, the independence of the republics and the collapse of communism in Eastern Europe. The second topic: we devoted this subject to talk about the position of the Soviets of the Second Gulf War and the international crowd to bring Iraq out in Kuwait led by the Americans.